STRUCTURAL GEOLOGY CONTROL OF HYDROTHERMAL ALTERATION AND MINERALIZATION IN BULAWAN SATU REGION, NORTH SULAWESI PROVINCE - Pradipta, Devito
Basemetals are necessary commodities to fulfill the needs of electronic, infrastructure, exchange rate, geopolitics, and pathfinder elements in gold exploration. Bulawan Satu Region is a consession area which is owned as a greenfield prospect and held the ongoing exploration by PT J Resources Nusantara. Bulawan Satu Region constituted relatively complex geological condition and NW-SE and NE-SW structural pattern which was formed as the manifestation of Sula Slab Subduction System and East Sangir Subduction System. The research is conducted to identify the structural geology pattern which is developed and impacted the hydrothermal alteration and mineralization in the region for exploration. The research was made through geological mapping, alteration, mineralization, geochemical analysis, geostatistics, and core logging. The research area is comprised of four intrusive rock units, three volcanic rock units, and four sedimentary rock units. Alteration zones which are found in the study area consist of silicification zone, calc-silicate zone, subpropyllitic zone, and argillic zone. Mineralizations which are found in the study area consist of basemetal minerals as basemetal veinlets, disseminated, and quartz-carbonate veinlets. Alteration zones and mineralizations in the study area indicated the presence of intermediate sulphidation epithermal system. Vein mapping in the study showed quartz-carbonate, quartz-limonite, quartz-hematite, quartz + calcite + pyrite vein are relatively NW-SE trending; while the quartz vein and calcite vein are relatively to NE-SW trending. Pearson’s product, exploratory data analysis, exploratory spatial data analysis, probability curve, and ordinary kriging method were conducted for geochemical and geostatistics analysis of surficial wall rock samples. Geochemical and geostatistics analysis showed that syn-mineralization structural geology which is formed by relatively N-S trending compressive force in form of strike slip fault, normal fault, and diatreme breccia are associated to the anomaly site of Cu, Pb, Zn, Ag, and Sb. The anomalies of Mn in the study area are affected by lithological factor. The strike slip and normal faults in the study area are interpreted to have taken role as hydrothermal fluid pathway hence the hydrothermal alteration intensity was found intensive around the damage zone of faults in study area.